2020
DOI: 10.1111/dme.14322
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of living with coexisting type 2 diabetes and severe mental illness: a scoping review

Abstract: Aims To map existing research‐based knowledge of everyday life and illness management among people with coexisting type 2 diabetes and severe mental illness, and to identify study designs, aims, populations and themes. Methods A systematic literature search was performed on 16 April 2019 using Medline, Embase, PsycINFO, Cinahl, the Cochrane Library, and the Web of Science to conduct a scoping review. Included studies were summarized with regard to the quantity of research, the study designs, aims, populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“… 30 The lower frequencies of healthy eating and physical activity among persons with psychiatric disorders and diabetes compared with persons with diabetes only are consistent with previous findings from a review which also found that people with diabetes and psychiatric disorders experience additional barriers to diabetes management related to the psychiatric disorder. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 30 The lower frequencies of healthy eating and physical activity among persons with psychiatric disorders and diabetes compared with persons with diabetes only are consistent with previous findings from a review which also found that people with diabetes and psychiatric disorders experience additional barriers to diabetes management related to the psychiatric disorder. 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 One study found increased level of diabetes distress in people with psychiatric disorders and diabetes, however without quantifying the proportion of people with diabetes distress. 15 Few studies have examined quality of life 16–18 and diabetes self-care 14 19 20 in people with psychiatric disorders and diabetes. High diabetes distress and low quality of life are likely to be even more prevalent in people with psychiatric disorders and diabetes compared with people with diabetes only, and psychiatric disorders may add additional barriers to diabetes self-management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this, being diagnosed with diabetes (type 1 or 2) increases the risk of developing a depression 6,7 . People diagnosed with both type 1 and 2 diabetes and severe mental illness (SMI) experiences high or very fluctuating levels of mental distress, affecting social function and daily living 8‐10 . In addition, distress is often caused by the experience of stigma and the lack of recognition of both conditions in treatment and personal care preferences as people with both conditions are less likely to receive diabetes services and care support, such as diabetes education and HbA 1c testing 2,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the first paper, Rønne et al . [2] describe the results of a systematic review of 23 studies of people living with comorbid type 2 diabetes and severe mental illness. During their analysis of the four qualitative and 19 quantitative studies, five themes emerged.…”
mentioning
confidence: 99%